Silicon nanosheets derived from silicate minerals: controllable synthesis and energy storage application - He, Yuanqing; Zhang, Zihan; Chen, Gen; Zhang, Ying; Liu, Xiaohe; Ma, Renzhi (Nanoscale, 2021)
Silicon plays a crucial part in developing high-performance energy storage materials, owing to a high specific capacity compared to carbon. Moreover, nanoscale silicon is beneficial for reducing the inherent disadvantage of large volume change during repeated lithiation/de-lithiation, while artificial synthesis methods usually involve complex procedures and high costs. On account of the abundant natural reserve and low cost, the manipulation of silicate minerals is a simple and economical approach to prepare silicon nanosheets. In this regard, this mini review introduces different classes of silicate minerals and summarizes some typical molten salt-assisted reduction methods and other valuable methods applied to prepare silicon nanosheets for energy storage. Finally, the challenges and perspectives in this field are also proposed. Progress in developing advanced Si nanosheets from silicate minerals for energy storage is reviewed.